How People with Depression Receive and Perceive Mental Illness Information: Findings from the Australian National Survey of Mental Health and Wellbeing - Graham, A.; Hasking, Penelope; Clarke, D.; Meadows, G. (Kluwer Academic Publishers, 2015)
Despite the recognised importance of accurate mental illness information in help-seeking and improving recovery, little is known about the dissemination of such information to people with depression. With a view to informing effective communication to those most in need, we explored the extent to which mental illness information is received by people with depression, its perceived helpfulness and we characterise those who do not receive such information. Using data from the Australian National Survey of Mental Health and Wellbeing we observed that mental illness information was received by 54.7 % of those with depression. Most (76.7 %) found it helpful. Pamphlets were the most frequently cited source of information. People who did not receive information were less educated, unlikely to have accessed mental health services and unlikely to believe they had mental health needs. Targeted information campaigns which shape perceptions of need in relation to depression have the potential to reduce the resultant disease burden.